Peran E-Commerce dalam Mendorong Peningkatan Volume Kiriman dan Penguatan Sektor Logistik - Diandra Anasya Putri; Dwi Novi Wulansari (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The growth of e-commerce expands physical order-fulfilment demand and pushes logistics networks to operate faster, more transparently, and flexibly. This article examines how e-commerce increases shipment volume and strengthens the logistics sector, focusing on Indonesia. It applies an integrative literature review and secondary-data analysis using open scientific articles and official publications from 2021–2026. The findings identify three mechanisms: expansion of the consumer and seller base, platformization that increases order frequency and fragmentation, and rising expectations for speed, tracking, accuracy, and easy returns. Global, Southeast Asian, and Indonesian data consistently associate digital-transaction growth with denser parcel flows. This pressure encourages investment in warehousing, sorting automation, fleets, tracking systems, and data integration. Nevertheless, logistics costs, infrastructure limitations, regional service gaps, and the complexity of last-mile and reverse logistics constrain sectoral strengthening. Data integration, infrastructure improvement, and standardized return services should therefore become priorities.